Three types of verbal logophoricity in African languages - Timothy Jowan Curnow (Studies in African Linguistics)
The term logophoric is most strongly tied to pronominal systems. However, most recent literature on logophoricity accepts the existence of verbal marking of logophoricity. Through examining the verbal logophoricity which has been reported in African languages, it can be seen that there are three different types of verbal marking: logophoric cross-referencing, first person logophoricity, and verbal logophoric affixation. These different types may appear as the only form of logophoric marking in a language, or they may combine with each other and with logophoric pronouns. Each of these types appears to have distinct properties and, hence, needs to be treated separately in typological literature.